The role of hyper-intermediate media in developing academic achievement in biology at the intermediate stage from the point of view of teachers (Journal of Hama University, 2025)
The goal of the current research is to identify the role of hypermedia in improving learners’ academic achievement in biology at the basic education stage from the point of view of teachers, and to identify the differences in the role of hypermedia in improving learners’ academic achievement in biology according to the variables of gender, academic qualification, and number of years of experience. And according to the variable of following training courses. The descriptive analytical method was used, The sample consisted of (147) male and female teachers of biology for the basic education stage. A questionnaire was used as a tool for the study, which consisted of (20) items. This questionnaire was directed to the teachers. The results showed: The role of hyper-intermediate media in improving learners’ academic achievement in biology in basic education from the point of view of teachers was significant. Differences also appeared between the average scores of the sample members on the questionnaire on the role of hyper-intermediate media in improving learners’ academic achievement in biology in basic education according to the gender variable in favor of females. Likewise, no differences appeared between the average scores of teachers on the questionnaire on the role of hyper-intermediate media in improving the learners’ achievement. Study in biology in basic education according to the academic qualification variable, This depends on the variable number of years of experience. While differences appeared according to the variable of following training courses in favor of teachers who purchased more than two training courses.
Keywords: hypermedia, academic achievement, biology.